Dynamic strategic marketing planning: the paradox of concurrently reconfiguring and implementing strategic marketing planning - Theoharakis, Vasilis; Zheng, Yuyan; Zhang, Long (Elsevier, 2024)
Traditional marketing planning may not be as effective in today’s challenging environments for achieving the dual imperative of meeting objectives and continuously improving market fit. Therefore, we introduce the concept of dynamic strategic marketing planning (DSMP) as a higher-order capability that requires the concurrent orchestration of marketing planning, senior management-led strategic implementation, and change as operationalized through the reconfiguration of processes and resources. With responses from 313 CEOs, we demonstrate that DSMP does overcome the innovativeness rigidities found in ordinary marketing planning capabilities. While DSMP is associated with higher levels of innovativeness, it also achieves higher levels of financial performance over ordinary marketing planning capabilities. Our findings seek to transform marketing planning practice by requiring that its implementation receives the attention of senior managers and combines reconfiguration processes that promote the renewal of plans and capabilities.
Keywords: Marketing planning; Strategic implementation; Dynamic capabilities; Reconfiguration